Investor sentiment and stock returns: some international evidence - Maik Schmeling (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
We examine whether consumer confidence - as a proxy for individual investor sentiment - affects expected stock returns internationally in 18 industrialized countries. In line with recent evidence for the U.S., we find that sentiment negatively forecasts aggregate stock market returns on average across countries. When sentiment is high, future stock returns tend to be lower and vice versa. This relation also holds for returns of value stocks, growth stocks, small stocks, and for different forecasting horizons. Finally, we employ a cross-sectional perspective and provide evidence that the impact of sentiment on stock returns is higher for countries which have less market integrity and which are culturally more prone to herd-like behavior and overreaction.
Keywords: G12; G14; G15; 330; Consumer confidence; growth stocks; investor sentiment; noise trader; predictive regressions; value stocks